Morphosyntactic analysis of Spanish to English translations in research abstracts of a graduate program of the Faculty of Humanities, Social Sciences and Guarani Culture of the National University of Itapúa (UNIHumanitas, 2019)
This descriptive research with qualitative approach and non-experimental design, aims to analyze the morphosyntactic characteristics of research summaries translated from Spanish to English, from a graduate program of the Faculty of Humanities, Social Sciences and Guarani Culture of the National University of Itapua, Paraguay. A morphemic breakdown, identification of translation errors and suggestions for improving the translations are made through Prator's hierarchy and a checklist. The improper use of electronic tools such as Google Translate® and errors of adaptation to the English language are present, as well as the absence of gender concordance, application of the literal translation technique and poor writing, both in the source and target language. It is proposed to create spaces to expand knowledge on the use of automatic translation programs, to emphasize subjects such as English-Spanish contrastive grammar and a better filtering of research summaries.
Keywords: translation; translation errors; Translation techniques; Electronic machine translation tools